The Influence of Media Effects in Television Content on the Audience (Herald of Journalism, 2026)
The main objective of the study is to identify contemporary trends in media consumption and to empirically analyze the specific impact of television content on various audience groups. The research idea is to explore the dependence of media content consumption culture within the media space on age, social, and technological factors, and to propose new models of audience interaction with media content.The study examines media effects theory in a modern context and provides a scientific and theoretical analysis of the media’s influence on individual and societal consciousness. From a practical perspective, the research findings may be useful for media professionals, content producers, and communication policy developers in formulating effective strategic plans that meet audience demands.The research methodology is based on surveys, comparative methods, and statistical analysis. Empirical data enabled the identification of the distinctive characteristics of media platforms, age-related differences, and audience preferences in content perception. The expected outcomes include the classification of media consumption models by age group, the systematization of the influence level of new media, and the recognition of television content as a significant source of information for particular social groups.The value of the research lies in enhancing the understanding of media culture dynamics, assessing audience informational preferences, and improving media and communication policies. The work can be regarded as an important practical contribution to the systematic study of media consumption processes in the context of the modern information society.
Keywords: media effect, media audience, media consumption culture, creative television content, multidimensional phenomenon of the media space.